Geografia cultural e música gaúcha: a construção da paisagem cantada da 13ª região tradicionalista do Rio Grande do Sul - Lorensi, Deise Caroline Trindade (2017)
Gaucho music expresses ideas, feelings and situations that enhance the state of Rio Grande do Sul. The experiences of the gaucho people arouse the interest of geographers due to the inclusion of historical, geographic and cultural aspects of society in the musical compositions, which reveal the gaucho cultural identity. Thus, the objective of this research is to identify cultural codes in gaucho music that comprise the actions, appropriations and representations of the regional space, which empower the construction of the cultural identity of the 13th Traditional Region of Rio Grande do Sul these days. In order to better define the answer to the research problem, the following specific objectives were outlined: (a) to discuss the existing relationship of studies in Cultural Geography with gaucho music, highlighting the cultural codes found in the lyrics; (b) to understand the importance of the cultural landscape to the process of poetic and musical creation, verifying the relationship between the artists (lyricists, composers, performers and musicians) and the landscape; and (c) to spatialize the main cultural codes as well as the elements materialized in the landscape. To achieve the research objectives, these two scientific methods were used: Phenomenology and Dialectics. Thus, in light of both phenomenological and dialectical methods, I aimed to understand the link between gaucho music and landscapes of the municipalities of the 13th Traditionalist Region. The possibilities presented by these methods seek to explain past issues, represented by the musical history of Rio Grande do Sul, and present issues as well, through the understanding of experience and cultural identity nowadays from the perspective of artists (singers/performers, musicians and composers) who were born or reside in the municipalities of the 13th Traditional Region of Rio Grande do Sul, therefore, showing the relationship of the musicians with the landscape. The development of this research followed some methodological stages. In the first stage, I worked on the literature review, which is based on guiding concepts, and conducted a survey of the artistic presentations in the municipalities of the 13th Traditionalist Region. In the second stage, I designed the research instrument, that is, a semi-structured interview. In the third stage, I conducted the interviews and collected data through snowball sampling in order to identify the subjects involved in the study, starting with the president of the Association of Musicians, Performers and Composers of Rio Grande do Sul. In the fourth stage, I analyzed the lyrics of songs that refer to the selected municipalities, trying to find out the relationship between the composition itself and the cultural landscape. The remaining data were analyzed in order to design and make maps of the culture materializations. Finally, it is concluded that gaucho music is an interesting way to know about different landscapes, social groups, their culture and symbology. The experiences revealed by the artists interviewed were essential for the development of this study because they provided a better understanding of the relationship between gaucho music and sungscape, which are consequences of the experiences and feelings developed in specific moments, thus working as stimuli for the poetic-musical creation.